Evaluation of anti-Mullerian hormone, antral follicle count and progesterone concentration during estrous cycle in Murrah buffaloes - KEKAN, P M; INGOLE, S D; NAGVEKAR, A S; BHARUCHA, S V; KHARDE, S D; KADAM, D P; GALDHAR, C N; MASARE, P S; DESHMUKH, S G (The Indian Journal of Animal Sciences, 2019)
An experiment was conducted to study the anti-Mullerian hormone (AMH) concentration, antral follicle count (AFC) and progesterone (P4) concentration during estrous cycle in Murrah buffaloes. Seven animals of 5–10 years were selected for the study. All the animals were synchronized as per the ovsync protocol and the pair of ovary of each animal was scanned by ultrasonography on 0, 3rd, 7th, 11th, 14th, 17th and 21st day of estrous cycle. Blood was collected on the same day to evaluate serum AMH and P4 concentration. The nonsignificant difference was observed in antral follicle count of 3–5 mm, 5–8 mm and total follicles count (> 3 mm), whereas, significantly lower mean values of >8 mm of antral follicles were recorded on the day of estrus (0.14 ±0.14) as compared to 3rd, 7th, 11th, 14th, 17th and 21st day of estrous cycle. The significant individual variation was recorded in average mean of 3 - 5 mm and total antral follicle count (>3 mm). However, the difference for 5 - 8 mm and >8 mm was nonsignificant. The positive correlation of low and high antral follicle count was observed in the present study. Two animals of low antral follicle count remained non pregnant and two animals showed 3 follicular waves during estrous cycle. The nonsignificant difference was recorded in AMH concentration during estrous cycle, whereas, individual variation in AMH concentration differ significantly. The progesterone concentration showed significant increase and decrease in values according to the stages of estrous cycle.